THE LATEST TRENDS OF EXTRADICTION AND THE PROBLEM OF IMPLEMENTING THEM IN THE POST-SOVIET SPACE - Abdulloev Parviz Sadulloevich; Buni Hisorak (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
All the post-Soviet states adopted a codification act on criminal procedure and improved the regulation of international cooperation in the extradition of persons within the framework of their national legislation, yet there are certain modern trends in the developed international cooperation on extradition among the post-Soviet states. A comprehensive disclosure of the legal nature, development of a more effective mechanism, identification of general development trends and formulation of conclusions and proposals for improving the institution of extradition is needed, based on comparative legal, concrete historical, and legal dogmatic methods, and on synthesis, deduction and induction, as well as a systemic and structural approach. There is a tendency to constantly improve the legal regulation of this issue; the present research concludes it is necessary to expand those trends that give more possibilities for extradition of persons to a foreign state.